A Godward life : savoring the supremacy of God in all of life - Piper, John, 1946- (Sisters, Or. : Multnomah Publishers, 1997)
A Godward Life is the first of three devotional volumes by John Piper, each feature 120 vignettes that focus on the radical difference it makes when we choose to live with God at the center of all that we do. Scripture-soaked and touching on the issues which most affect our lives today, A Godward Life is a call for all believers to live their lives in conscious and glad submission to the sovereignty and glory of God.
[Vol. 1]. Savoring the supremacy of God in all life -- Vol. 2. Savoring the sustenance of God in all of life.
Includes bibliographical references and indexes.
Keywords: Christian life